Transformational Leadership and Teacher’s Performance: The mediating role of motivation and commitment - Shahrir Bin Jamaluddin, Jumadil Saputra, Nor Zanariah Talib, Norhannan Binti Ramli, Zaharah Binti Hussin, (Opción, 2019)
This multilevel study examines the psychological mechanisms (i.e., motivation and commitment) that might underlie the relationship between transformational leadership and job performance. Models were tested using the sample of teachers, n = 266 embedded in 55 teams from secondary schools in Malaysia. Using hierarchical linear modeling (HLM), we found that there was a cross-level effect of transformational leadership on motivation, commitment and performance. In conclusion, our finding proposes that transformational leadership is a vital organizational leadership style construct, and acts to enhance teachers’ performance via psychological boost.